Hubungan Pembelajaran Daring dengan Prestasi Belajar Siswa pada Masa Covid 19 di SMANegeri 7 Singkawang - liliek fauziah, liliek; Fatmawani, Florensia; Yuliani (Faculty of Health Science and Technology, University of Jenderal Achmad Yani, 2023)
The learning process at SMA Negeri 7 Singkawang during the pandemic period July 2020 to June 2021 carried out online learning. During online learning there was a decline in student achievement caused by gadgets, expensive quotas and inadequate internet network factors. The purpose of this study was to determine the relationship between online learning and student achievement during the covid 19 period. This study is a quantitative study using a descriptive correlative design with a cross sectional approach, the population in this study was grade 12 students and the number of samples was 145 respondents with random sampling technique. Data analysis using Spearman Rank test. The results showed that more than half of the respondents (56.8%) considered online learning to be ineffective and more than half of the respondents (70.3%) had good learning achievement. The results of the Spearman Rank test obtained a value (p value = 0.000 < 0.005 and r = 0.378) so that Ha is accepted, then there is a weak relationship between online learning and student achievement at SMA Negeri 7 Singkawang. Online learning becomes ineffective because it is caused by several factors, namely slow internet network, expensive internet quota prices, student behavior is difficult to monitor so they become inactive in learning. It is hoped that the school and family will work together to improve student learning achievement to be more effective.